UPAYA HUKUM PENINJAUAN KEMBALI OLEH TERPIDANA DALAM KUHAP YANG BOLEH DI AJUKAN DUA KALI - Papang Sapari (The Juris, 2020)
The purpose of this research is to find out what is the reason for the filing of a criminal case review (PK) and how the arrangements for a judicial review (PK) in the Criminal Procedure Code can be filed twice. Using the normative juridical research method, Constitutional Court Decision No. 34 / PUU-XI / 2013 has opened a PK room not only once as regulated so far by Criminal Procedure Code/KUHAP, Article 268 paragraph (3) of the Criminal Procedure Code so that PK can be carried out many times as long as a novum is found and filed even though the previous PK has been carried out. Responding to the Constitutional Court Decision, the Supreme Court issued SEMA No.7 of 2014 concerning Submission of Petitions for Reconsideration in Criminal Cases. Through this SEMA, the Supreme Court reminded that the provisions of the PK only once outside of Article 268 of the Criminal Procedure Code were canceled by the Constitutional Court, therefore PK criminal cases (in the same case) which were declared unacceptable more than 1 (once).